(untitled) (Experimental biology, 2026)
This study presents the results of mapping the distribution of economically important and quarantine weed species in southern Kazakhstan. Field surveys were conducted in the Almaty, Zhetysu, Zhambyl, and Turkestan regions, covering agricultural lands, roadside habitats, fallow fields, and irrigated areas. Georeferenced sampling was carried out to determine the current distribution range and infestation level of major weed species. A total of 1,078 specimens of Rhaponticum repens (Russian knapweed), 1,153 specimens of Ambrosia artemisiifolia (common ragweed), and 1,027 specimens of Cuscuta campestris (field dodder) were collected and analyzed. Weed distribution mapping was performed using QGIS 3.28, while geographic coordinates were processed with the Lat Lon Tools plugin. The resulting thematic maps enabled visualization of infestation hotspots and distribution patterns across the study area. The results showed that transportation corridors, irrigated agroecosystems, and intensively managed agricultural landscapes represent major pathways for weed dispersal. R. repens was primarily associated with arid and foothill environments, C. campestris was mainly distributed in irrigated croplands and roadside habitats, whereas A. artemisiifolia exhibited a fragmented but expanding distribution near urbanized and highly disturbed areas. The study demonstrates the value of GIS-based mapping as an effective tool for monitoring quarantine weeds, assessing phytosanitary risks, and supporting weed management strategies in southern Kazakhstan.